Alternative promoter usage and splicing options result in the differential expression of mRNAs encoding four isoforms of chicken VBP, a member of the PAR subfamily of bZIP transcription factors. - Burch, J B (1994)
We previously isolated a set of overlapping cDNA clones that encoded a unique open reading frame for the chicken VBP transcription factor. We now report the isolation of a cDNA clone that encodes a complete open reading frame for a VBP isoform that differs from the previously reported sequence at both the amino-terminal and carboxyl-terminal ends. An analysis of the VBP gene revealed that the two different amino-terminal sequences map to alternative first exons and that the two different carboxyl-terminal sequences reflect an optional splicing event which can occur only on transcripts that are polyadenylated at the more distal of two polyadenylation sites. An RT-PCR analysis further revealed that a total of four VBP isoforms are encoded by the combinatorial use of these two splicing options. The mRNAs for these four isoforms are differentially expressed in different tissues and cell types. We provide evidence that one function of the amino-terminal domains is to impose cell type specificity on a core transactivation domain that is present in all four isoforms. Since it is known that VBP can heterodimerize with other members of the PAR subfamily of bZIP factors, our evidence for four VBP isoforms greatly expands the number of complexes that may be used to effect transcriptional regulation through PAR-factor binding sites.